The SAURON project - XI. Stellar Populations from Absorption Line Strength Maps of 24 Early-Type Spirals - Peletier, R; Falcon-Barroso, J; Bacon, R; Cappellari, M; Davies, R; Zeeuw, P; Emsellem, E; Ganda, K; Krajnovic, D; Kuntschner, H; McDermid, R; Sarzi, M; et al. (2007)
We present absorption line strength maps of a sample of 24 representative early-type spiral galaxies, mostly of type Sa, obtained as part of the SAURON survey of nearby galaxies using our custom-built integral-field spectrograph. Using high-quality spectra, spatially binned to a constant signal-to-noise, we measure several key age, metallicity and abundance ratio sensitive indices from the Lick/IDS system over a contiguous two-dimensional field including bulge and inner disc. We present maps of H beta, Fe 5015 and Mg b, for each galaxy The absorption line maps show that many galaxies contain some younger populations (<= 1 Gyr), distributed in small or large inner discs, or in circumnuclear star forming rings. In many cases these young stars are formed in circumnuclear mini-starbursts, which are dominating the light in the centres of some of the early-type spirals. These mini-starburst cause a considerable scatter in index-index diagrams such as Mg b- H beta and Mg b -Fe 5015, more than is measured for early-type galaxies. We find that the central regions of Sa galaxies display a wide range in ages, even within the galaxies. 50% of the sample show velocity dispersion drops in their centres. All of the galaxies of our sample lie on or below the Mg b- $σ$ relation for elliptical galaxies in the Coma cluster, and above the H beta absorption line - $σ$ relation for elliptical galaxies. If those relations are considered to be relations for the oldest local galaxies we see that our sample of spirals has a considerable scatter in age, with the largest scatter at the lowest $σ$. This is in disagreement with highly inclined samples, in which generally only old stellar populations are found in the central regions. All this can be understood if ... (see paper for rest of abstract)